Pluripotency properties of embryonic stem cells isolated from stage X blastoderm of Mazandaran native chicken - Jahanpanah, M.; Pourasgari, F.; Mohammadi-sangcheshmeh, A.; Ardeshirylajimi, A.; Azarnia, M.; Sharifi, S. D.; Soleimani, M. (Cellular and Molecular Biology, 2014)
The aim of this study was to isolate Embryonic Stem Cells (ESCs) from native chicken and to characterize their pluripotency properties through the cellular and molecular markers. Samples obtained from fertilized eggs from Mazandaran native hens. Cells were isolated from area of pellucida from stage X native hens’ blastoderm. Then the cells were cultured on inactivated mouse SNL feeder cells in the presence of LIF, IGF-1, bFGF, CNTF, OSM, SCF, Il-6, and Il-11 growth factors. The native chickens’ ESCs colonies were picked up and subsequently passaged. To characterize the cells, they were analyzed for their alkaline phosphatase activity, and also for the expression of SSEA-4, and TRA-1-60 as embryonic-specific markers at the protein level. Furthermore, the expression of pluripotency (cPouV, Sox2, and Nanog) and cell lineage specific (Cvh, Brachyury, and Gata6) gene markers was evaluated at the level of mRNA using quantitative RT-PCR. Isolated cells were passaged repeatedly and successfully up to ten passages. The stemness of embryonic cells has been approved by the activity of the alkaline phosphatase, presence of the SSEA-4, and TRA-1-60 protein, and expression of the molecular marker (cPouV, Nanog, and Sox-2) genes. The spontaneous differentiation of chicken ESCs confirmed the pluripotecy of the cells in differentiation into specialized cell lineages. Our observation showed that ESCs can be isolated successfully from stage X blastoderm of Mazandaran native chickens and these cells maintain their stemness properties during multi-passages in vitro.